2016
DOI: 10.1002/ange.201608429
|View full text |Cite
|
Sign up to set email alerts
|

Erzeugung zweifach koordinierter Bor(I)‐Einheiten durch Fragmentierung eines molekularen Tetra‐Bor(I)‐Quadrats

Abstract: Die Reduktion des Carbenboranaddukts [(cAAC)BBr 2 (CN)] (cAAC = 1-(2,6-Diisopropylphenyl)-3,3,5,5-tetramethylpyrrolidin-2-yliden) verlief sauber zur Tetra(cyanoborylen)verbindung [(cAAC)B(CN)] 4 ,w elche einen zwçlfgliedrigen (BCN) 4 -Ring aufweist. Die Analyse der Kohn-Sham-Molekülorbitale zeigte eindeutige Boryleneigenschaften der B I -Atome.E inerseits reduzierte [(cAAC)B(CN)] 4 zwei ¾quivalente AgCN unter Bildung von [(cAAC)B(CN) 3 ], andererseits fragmentierte es in der Reaktion mit IMeMe (1,3,4,5-Tetrame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 49 publications
0
13
0
2
Order By: Relevance
“…Particularly,t he nitrogen analogues, phosphazenes II,have attracted significant attention owing to the wide variety of applications as precursors of fireproof polymers [2] and as non-nucleophilic strong bases. [11] Among these,w eh ave been interested in the lightest homologue in the series,t he boron-centered phosphonium ylide V.P hosphorus bora-ylide V can also be regarded as aborylene stabilized by aphosphine ligand. [5] Several stable phosphanylidene-phosphoranes IV [6][7][8] have also been used as phosphinidene transfer agents.B oth the strong s-a nd p-donor character of IV make them excellent ligands for transition metals [9] and for the stabilization of low-valent highly reactive species.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly,t he nitrogen analogues, phosphazenes II,have attracted significant attention owing to the wide variety of applications as precursors of fireproof polymers [2] and as non-nucleophilic strong bases. [11] Among these,w eh ave been interested in the lightest homologue in the series,t he boron-centered phosphonium ylide V.P hosphorus bora-ylide V can also be regarded as aborylene stabilized by aphosphine ligand. [5] Several stable phosphanylidene-phosphoranes IV [6][7][8] have also been used as phosphinidene transfer agents.B oth the strong s-a nd p-donor character of IV make them excellent ligands for transition metals [9] and for the stabilization of low-valent highly reactive species.…”
mentioning
confidence: 99%
“…[3,4] In contrast, the heavier analogues of I,s ila-ylides III,p resent an enhanced silylenoide character with at ransition-metal-like behavior owing to the weak SiÀPinteraction without any SiÀP p-bond character. [11] Among these,w eh ave been interested in the lightest homologue in the series,t he boron-centered phosphonium ylide V.P hosphorus bora-ylide V can also be regarded as aborylene stabilized by aphosphine ligand. [10] Despite numerous examples of phosphonium ylides with Group-14-16 elements,t he synthesis of Group 13 elementbased stable phosphorus ylides is still extremely rare.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[12] Since the first isolation of ab orylene stabilized by two cyclic alkyl-amino carbenes (cAAC) VII by Bertrand et al, [13] several stable borylene complexes with different ligands have been described VIII, IX. [16,17] Of particular interest, these boron species,b eing isoelectronic with amines,p resent an ucleophilic three-coordinate boron center with al one-pair, [13,14] and it has been clearly demonstrated that they can be used as s-donating ligands for transition metals. [16,17] Of particular interest, these boron species,b eing isoelectronic with amines,p resent an ucleophilic three-coordinate boron center with al one-pair, [13,14] and it has been clearly demonstrated that they can be used as s-donating ligands for transition metals.…”
mentioning
confidence: 99%
“…[1] Braunschweig gehçrt ab 2017 außerdem dem International Advisory Board des European Journal of Inorganic Chemistry an. 1991-1992 war er Postdoc bei Michael F. Lappert an der University of Sussex;d anach kehrte er nach Aachen zurück, um sich bei Paetzold zu habilitieren;1998 wurde er in Aachen Dozent.…”
unclassified